(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
The taxonomic study of Early Pliocene ostracods from the Valdelsa Basin (Tuscany, central Italy) has been performed on 12 samples. Fifteen species, referable to eight genera, have been identified. Eight are known species (Darwinula stevensoni (Brady & Robertson), Candona (Neglecandona) neglecta Sars, Pseudocandona albicans (Brady), Pseudocandona cf. P. eremita (Vejdovsky), Candonopsis arida Sieber, Ilyocypris cf. I. monstrifica (Norman), Ilyocypris bradyi Sars and Mixtacandona cf. M. tabacarui Danielopol & Cvetkov. Six species are new and have been referred to the genera Cyprideis (C. rectangularis n. sp.), Paralimnocythere (P. dictyonalis n. sp. and P. toscana n. sp.) and Candona (Neglecandona) [C. (N.) dorsoreticulata n. sp., C. (N.) subtilis n. sp., C. (N.) sambucensis n. sp.]. Two species have been left in open nomenclature, due to scarcity of material and poor preservation (Candona (Neglecandona) sp. and Cyclocypridinae indet.). The Early Pliocene ostracods of the Valdelsa Basin show palaeobiogeographical affinities with both the Central and Western European faunas and the Balkan candonids. The occurrence of ostracods with Balkan and Eastern Europe affinity is also known from the more ancient Italian deposits of the late Tortonian-early Messinian and latest Messinian age. In the first case, the ostracods widespread by passive dispersal, whereas during the latest Messinian they actively dispersed in the Palaeo-Mediterranean area due to its connection with the central and eastern Paratethyan domains.